THE ROLE OF AL-WASHLIYAH 12 PERBAUNGAN EDUCATORS IN PRODUCING RELIGIOUS LEADERS IN SERDANG BEDAGAI - Astri Hikmayati Okastina; Yusnaili Budianti; Salminawati Salminawati (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to analyze the role of educators in producing religious leaders in Al-Washliyah 12 Perbaungan through the application of curriculum, learning strategies, and supporting factors, inhibitions, and solutions to overcome the obstacles faced. The method used in this study is a qualitative method with a phenomenological approach, which is descriptive and analytical. Data collection techniques are carried out through observation, interviews, and document studies. The data sources in this study are primary data sources and secondary data, obtained from Al-Washliyah 12 Perbaungan. The results of the study show that in Al-Qismul Aly Al-Washliyah 12 Perbaungan, the Diniyah curriculum (Yellow Book) is implemented as a characteristic of madrasas and the National curriculum.The learning strategy used by educators is a combination of classic methods such as bandongan, sorogan, and lectures, with modern methods to adapt to the times. The results of the study also show that the alumni of Al-Qismul Aly Al-Washliyah 12 Perbaungan, have good science and morals. Take part as an ustad, educator, and contribute to the community.The supporting factors for the success in implementing the Diniyah curriculum are the role of the head of the madrasah, competent educators in the field of the Yellow Book, a structured curriculum, and a supportive environment. The obstacles faced are the differences in the academic background of students and the limited understanding of Nahwu Shorof. As a solution, supporting programs such as the Yellow Book Daurah, ability selection for new students, and Qira'atul Kutub extracurricular activities are carried out to increase students' understanding of the yellow book.